LAG-3: a very singular immune checkpoint - Lui, Y; Davis, S (Springer Nature, 2018)
The mechanism of action of the lymphocyte checkpoint protein LAG-3 was always rather mysterious. It now seems to operate at least in part by recognizing and suppressing responses to stable complexes of peptide and major histocompatibility complex class II.